2012
DOI: 10.1097/prs.0b013e3182547aaf
|View full text |Cite
|
Sign up to set email alerts
|

Postmastectomy Breast Reconstruction in the Irradiated Breast

Abstract: Therapeutic, III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 20 publications
3
18
0
Order By: Relevance
“…Not surprisingly, this indicates that those surveyed preferred the minimal amount of scarring possible. The DIEP is often considered the gold standard for breast reconstruction by many surgeons [ 5 ] for its aesthetic result and natural ptosis. However, it has been reported that surgeons may overestimate the result of a technically more advanced reconstruction [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Not surprisingly, this indicates that those surveyed preferred the minimal amount of scarring possible. The DIEP is often considered the gold standard for breast reconstruction by many surgeons [ 5 ] for its aesthetic result and natural ptosis. However, it has been reported that surgeons may overestimate the result of a technically more advanced reconstruction [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Body image has been shown to be a key factor in determining differences in quality of life when comparing mastectomy and breast conserving therapy [ 4 ]. Regardless of the reconstructive technique, the overall patient satisfaction rates are typically high post breast reconstruction [ 5 6 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, reconstruction of the lost breast is generally performed. Methods of breast reconstruction are classified into two genres: reconstruction by the transfer of autologous tissues [ 2 , 3 ] and reconstruction with artificial materials [ 4 6 ]. The latter genre is less invasive than the former.…”
Section: Introductionmentioning
confidence: 99%
“…The principal drawback from the patient’s perspective of the use of the latissimus flap as an option for breast reconstruction is the incisional scar. Although ultimate patient satisfaction with latissimus reconstruction is quite high, 14 design and placement of the skin island may have a favorable impact on the appearance of the scar and the patient’s perception of the same. The original design by Bostwick et al 1 was a vertical oblique orientation and subsequently a transverse and superiorly oriented location of the flap on the back, with the latter an attempt to conceal the scar beneath the brassiere.…”
Section: Discussionmentioning
confidence: 99%